Pharmacokinetic Evaluation of Telmisartan and Cilnidipine Bilayer Tablet in A Rabbit Model: Pharmaceutical Science-Pharmacy - Kadu, Pooja; Zalte, Amar; Gulecha, Vishal (International Journal of Life Science and Pharma Research, 2023)
Hypertension is a chronic medical condition affecting a significant proportion of the global population. It is a major risk factor for cardiovascular diseases, stroke, and kidney failure. Telmisartan and cilnidipine combination are commonly used in managing hypertension due to their complementary mechanism of action. Therefore, a bilayer tablet design that enhances the pharmacokinetic profile of cilnidipine as a sustained-release drug while telmisartan act as an immediate-release drug may provide a better therapeutic option for hypertension management. We aim to evaluate the pharmacokinetic parameters of the bilayer tablet of Telmisartan and Cilnidipine. Our objective is to observe the bioavailability of the bilayer tablet in rabbit plasma. The formulation aims to achieve an immediate release effect for Telmisartan and a sustained release effect for Cilnidipine. The solubility and bioavailability of Telmisartan were enhanced by complexation with beta-cyclodextrin. To achieve our aim, we observe the drug concentration in rabbit plasma. Telmisartan is an angiotensin receptor blocker, while Cilnidipine is a calcium channel blocker. The pharmacokinetics of the drugs were evaluated in New Zealand rabbits following oral administration. Systemic drug bioavailability was assessed, and an HPLC method was developed to estimate Telmisartan and Cilnidipine’s plasma concentration simultaneously. A Gemini C-18 column (250 mm X 4.6 mm X 5 microns) Phenomenex was used for peak separation. The mobile phase consisted of acetonitrile with phosphate buffer pH 3.5 v/v, with a flow rate of 1.5 ml per minute. The calibration curve analysis indicated a correlation coefficient of 0.9996 and 0.9997 for Telmisartan and Cilnidipine, respectively. The pharmacokinetics of the optimized batch, including Cmax, Tmax, and AUC values, were compared to those of the pure drug. Drug concentration was detected using a DAD detector with an excitation wavelength of 241nm. No interaction was observed between the drugs and excipients. The in-vivo study of the formulation showed higher bioavailability, indicating that the developed bilayer tablet formulation could be an effective means of delivering Telmisartan and Cilnidipine.